Experimental and numerical study on the heat transfer characteristics of waxy crude oil in a 100, 000 m3 double-plate floating roof oil tank. (25th May 2018) - Wang, Min; Yu, Bo; Zhang, Xinyu; Yu, Guojun; Li, Jingfa
Highlights: Experimental and numerical studies are performed to investigate the heat transfer characteristics in the tank. Variations of the rheological behavior and phase change are considered in the model. Evolutions of the flow and heat transfer in the tank are studied in detail. Variations of the heat flux on tank top, bottom and wall are analyzed. Abstract: 100, 000 m 3 double-plate floating roof oil tank is the most widely used tank for waxy crude oil storage in petroleum industry. A detailed study on the heat transfer characteristics of waxy crude oil in the tank is of great significance for storage safety, tank structure optimization and energy conservation. In this paper, experimental and numerical approaches are jointly adopted to study the heat transfer characteristics in the tank for a long-term storage. On the aspect of experimental investigation, thermal sensors are installed in the tank to monitor the oil temperature and obtain the temperature drop curve and vertical temperature distribution. On the aspect of numerical investigation, with the consideration of non-Newtonian behavior and phase change (wax precipitation or melt), physical and mathematical models for the heat transfer characteristics of waxy crude oil in a double-plate floating roof oil tank are established. Taking a 100, 000 m 3 double-plate floating roof oil tank as example, the evolution of temperature, turbulent kinetic energy and turbulent viscosity is studied, and the variations of the heat flux on tank top, tank bottom and tank wall are analyzed in detail.